Should research experience be used for selection into graduate school: A discussion and meta‐analytic synthesis of the available evidence. (14th October 2020) - Miller, Anthony; Crede, Marcus; Sotola, Lukas K.
Abstract: Prior research experience is widely considered by graduate school admissions committees in the United States of America. Here, we use meta‐analytic methods and data from 18 unique samples and a total sample size of 3, 525 students to shed light on the validity of prior research experience as a predictor of graduate school performance. Prior research experience was largely unrelated to academic performance ( ρ  = .01, k  = 8, N  = 1, 419), degree attainment ( ρ  = .05, k  = 3, N  = 140), professional/practice performance ( ρ  = .06, k  = 4, N = 1, 120), and publication performance ( ρ  = .11, k = 7, N  = 1, 094). We also discuss whether consideration of prior research experience may unfairly disadvantage the students with lower levels of SES, students with childcare or eldercare responsibilities, and students from institutions at which research opportunities are limited.